ПРИНЦИПИ ПОДАТКОВИХ ПРАВОВИХ ВІДНОСИН В УКРАЇНІ: РЕАЛІЗАЦІЯ ТА ШЛЯХИ УДОСКОНАЛЕННЯ - Хатнюк, Наталія Сергіївна (SUPREMANCE OF LAW, 2017)
In the scientific article to research legal nature of inviolable fundamental positions which translate in legal and economic space ideological essence of the unique system of tax intercommunications of participants of tax relations and appear important orientirom of progress of tax legislation trends is investigational in the article. The study enabled the author’s approach to formulate specific guidelines for the classification of ideas of tax legal relations as initial bases for their implementation and stabilization for the effective filling of public funds. This approach is based on mapping legal reality in the consciousness of a common system of tax legal relationships and reliable facts, which requires strengthening the law on State responsibility to the taxpayers.
Keywords: fundamental principles; principles of tax right; principles of taxation; principles of tax; principles of the tax system; principles of tax legal relations